The Relationship of Providing Education on Appropriate Complementary Feeding with the Nutritional Status of Infants 6-12 Months of Age - Rugun Patricia Sinaga; Sabna Rahmi; Yeni Hesnika Gulo; Ruth Pinkkan Nick Br Siregar; Debi Novita Siregar (Indonesian Journal of Global Health Research, 2025)
Infants aged 6–12 months are in a critical stage of growth and development, where proper complementary feeding alongside exclusive breastfeeding plays a key role in supporting normal weight gain. Educating mothers on the correct patterns and selection of complementary foods can improve their knowledge and behavior in meeting their babies' nutritional needs. Objective: To determine whether there is a relationship between providing education and maternal knowledge about patterns and selection of complementary foods with nutritional status in infants aged 6-12 months. Methods: This study used quantitative research with a quasi-experimental design involving a pre-test group and a post-test group without a control group. The population includes all mothers who have babies aged 6-12 months totaling 70 respondents. The sampling method uses Non Probability Sampling with Purposive Sampling type. Data collection applied in this study included pretest and postest stages, namely measuring anthropometry in infants (Height and Weight) and providing education to mothers in the form of counseling using leaflets. Data were analyzed using univariate and bivariate. Results: Based on the Wilcoxon test, the obtained p-value is 0.001, which is less than 0.005. This indicates that the null hypothesis (H0) is rejected. Therefore, it can be concluded that providing education on appropriate complementary feeding has a significant effect on infants aged 6-12 months.